Demokrati og politisk deltagelse - Svensson, Palle (Politik, 2015)
Democracy and political participation are closely related, but both the understanding of them and their relationship is disputed. Two conceptions of democracy – in this article labeled ‘democratic revisionism’ and ‘participatory democracy’ – compete for attention. In the article it is shown how the rst conception of de- mocracy as elite competition developed after World War II. It is further explained how participatory democ- racy developed as a critique of the rst conception. It is also shown how the desirability and the functions of political participation are perceived di erently according to the two conceptions of democracy. Various forms of political participation are discussed, and it is shown how the concept of participation in political science and sociology has been developed to include an increasing number of activities. On this basis, the extent and social distribution of various forms of political participation in Denmark is examined. Finally, it is discussed whether the idea of participatory democracy forms the basis of Danish democracy today. It is concluded that the leaders of the main political parties are reluctant to give up power and that the self-perception of Danish democracy is mainly based on the idea of representative democracy that focuses on elite competition.